The life and art of Albrecht Dürer - Panofsky, Erwin, 1892-1968 (Princeton classic editions., 2005)
This classic text presents the life, times, and works of Albrecht Durer. Through the skill and immense knowledge of Erwin Panofsky, the reader is dazzled not only by Durer the artist but also Durer in a wide array of other roles, including mathematician and scientific thinker. Originally published in 1943 in two volumes, The Life and Art of Albrecht Durer met with such wide popular and scholarly acclaim that it led to three editions and then, in 1955, to the first one-volume edition. Without sacrifice of text or illustrations, the book was reduced to this single volume by the omission of the Handlist and Concordance. The new introduction by Jeffrey Chipps Smith reflects upon Panofsky the man, the tumultuous circumstances surrounding the creation of his masterful monograph, its innovative contents, and its early critical reception. Erwin Panofsky was one of the most important art historians of the twentieth century. Panofsky taught for many years at Hamburg University but was forced by the Nazis to leave Germany. He joined the faculty at the Institute for Advanced Study in 1935, where he spent the remainder of his career and wrote The Life and Art of Albrecht Durer. He developed an iconographic approach to art and interpreted works through an analysis of symbolism, history, and social factors.